Pengaruh Pertumbuhan Penduduk dan Pertumbuhan Ekonomi Terhadap Tingkat Pengangguran di Kota Pontianak - Lidiya Rima Ranti; Astrid Astrid; Dewi Yanti; Yusawinur Barella (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the effect of population growth and economic growth on the unemployment rate in Pontianak City through literature review and ethnographic methods. The research findings show that the theory of population growth explains how demographic dynamics can affect the availability of job opportunities. Rapid population growth in Pontianak City has had an impact on the increase in the labor force, which is not accompanied by adequate economic growth, thus causing an increase in the unemployment rate. In addition, other factors such as the quality of human resources, the distribution of development, and the availability of infrastructure also affect employment opportunities in the region. Efforts to control the rate of population growth through population programs, such as increasing access to education and health as well as empowering women, are expected to reduce the unemployment rate and improve the welfare of the community in Pontianak City in a sustainable manner.